Idea uniwersytetu kształcącego ludzi zaangażowanych w pracę - Kulikowski , Konrad (Studia Edukacyjne, 2020)
The first part of this article introduces the work engagement concept in a framework of the Job Demands-Resources Theory and discusses a relation between work engagement and job crafting. Next, the author presents the hypothesis that university education can form engaged employees by enhancing students’ self-efficacy beliefs about their ability to effectively crafting their future job environments. On the basis of the Social Learning Theory the author proposed three possible methods on how the university community could promote job crafting behaviors among students. These methods are: trainings and persuasions, modeling, or observation of how university top researchers work, and allowing students to experience success in changing different aspects of the university environment.